Draft Annual Plan 1986-87 Volume I Statement of Figures State Planning Commission Tamil Nadu - Planning Commission (Planning Commission, 1986)
The Annual Plan for 1986-87, the second year of the Seventh Five-Year Plan, has been formulated keeping in view the policy and programme thrust for the Seventh Plan as set out in the approach document of the Union Planning Commission. The basic priorities for the Seventh Plan, viz., food, work and productivity are reflected in the investment strategy in areas of national importance such as in Agriculture and allied Services, Poverty _ alleviation Programmes, Irrigation and Power and upliftment of Scheduled Castes and Scheduled Tribes. Within the constraint of resources, provision has been made to expand the programmes specially for the benefit of the weaker sections of the community and the backward areas. The logic underlying the formulation of the Annual Plan has been one of promoting Growth with Stability. The Plan includes a number of measures and programmes designed to increase the income and consumption levels of the poor. The departmental programmes competing for inclusion in the Plan under the various sectors have been carefully screened and new starts has been considered on a selective basis. Schemes weighted towards staff were not favoured except where such addition would mean increase in efficiency in the production of goods or services.
Statement of Figures
Government of Tamil Nadu